2014
DOI: 10.5740/jaoacint.13-019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ochratoxin A in Cocoa Beans Using Immunoaffinity Column Cleanup with High-Performance Liquid Chromatography

Abstract: A method was developed and validated for the determination of ochratoxin A (OTA), a fungal metabolite, in cocoa beans of high fat content. The sample was extracted by blending with a 1% sodium bicarbonate solution (pH 10) followed by ultrasonication, and the sample was defatted by treatment with a flocculant. The defatted sample was purified using immunoaffinity column chromatography, and OTA was detected using HPLC with fluorescence detection. The method was fully optimized, validated, and quality controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…These authors analyzed 32 cocoa bean samples from the Western North and Western South regions of Ghana and found OTA contamination ranging from 0.186 μg/kg to 4.650 μg/kg. In agreement with previously reported studies, the present study demonstrated comparable variability in the range and levels of OTA contamination across the cocoa-growing regions and crop seasons [ 34 , 36 , 41 , 55 , 56 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These authors analyzed 32 cocoa bean samples from the Western North and Western South regions of Ghana and found OTA contamination ranging from 0.186 μg/kg to 4.650 μg/kg. In agreement with previously reported studies, the present study demonstrated comparable variability in the range and levels of OTA contamination across the cocoa-growing regions and crop seasons [ 34 , 36 , 41 , 55 , 56 ].…”
Section: Resultssupporting
confidence: 93%
“…Similarly [ 34 ], found OTA in 54 of 59 ready-to-sell cocoa bean samples from Nigeria, with concentrations ranging from 1.0 μg/kg to 277.5 μg/kg. Additionally [ 56 ], examined cocoa bean samples from Trinidad and Tobago between 2007 and 2010 and found OTA contamination ranging from 2.67 ± 0.18 μg/kg to 14.61 ± 0.39 μg/kg. Conversely [ 41 ], indicated that the range and levels of OTA contamination in cocoa beans varied relatively narrowly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…fungi. While PAT is predominantly found in fruits and fruit-based products [7], OTA is considered one of the most prevalent contaminants in the food chain, occurring in cereals, grape, coffee, spices, and cocoa, as well as in foods of animal origin [8][9][10][11][12]. Epidemiological evidence suggests that OTA is implicated in the pathogenesis of renal diseases including Balkan endemic nephropathy, kidney tumours occurring in endemic regions of the Balkan Peninsula, and chronic interstitial nephropathy occurring in Northern African countries and likely in other parts of the world [13,14].…”
Section: Introductionmentioning
confidence: 99%